Evaluating Learning Space Designs for Flipped and Collaborative Learning: A Transactional Distance Approach - William Swart; Ken MacLeod (MDPI AG, 2021)
Problem-based learning is the latest name for a teaching philosophy that is as old as Ancient Greece. Whether you call it Socratic Inquiry, case-based teaching, problem-based learning, interactive group learning, or "flipped" learning, the essential concept is to encourage the student to collaborate in applying their gained knowledge to solve a problem. As traditional lecture-based teaching has been challenged, the design of classrooms has been called into question. A flat or tiered room is not seen as an ideal setting for collaborative work. In our own College of Business, several traditional classrooms were converted to problem-based learning classrooms at considerable expense. This paper evaluates, using measures based on Michael G. Moore's theory of transactional distance, whether moving flipped classes into these high-tech classrooms improves the collaborative learning experience. Transactional distance can be defined as the barriers that exist to a student's engagement with their learning experience. These barriers arise due to the interaction between students and the teacher, other students, the subject matter content, and instructional technology being used. Our results suggest that, from a student engagement and outcome standpoint, the investment in costly high-tech classrooms is not warranted-a welcome result in times when university budgets are stretched to the limit.